PENGARUH GREEN MARKETING MIX TERHADAP VALUE PERCEPTION DAN MINAT BELI KONSUMEN THE BODY SHOP DI KOTA MATARAM - Maya Triana; Sulhaini Sulhaini (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
This research examined the effect of Green Marketing Mix, Value Perception and Intention To Buy cosmetic product of The Body Shop in Mataram City. This research is specifically aimed at determining the significance of the effect of Green Marketing Mix on Value Perception and Intention To Buy on cosmetic product at The Body Shop in Mataram City. The population of this study was customer of cosmetic product of The Body Shop in Mataram City, contain 100 respondents using purposive sampling method. The instrument in this study tested using Confirmatory Factor Analysis, while the reliability test using Cronbach Alpha. This research using Structural Equation Modelling employing SmartPLS program to test the hypothesis. The research results showed that Green Marketing Mix significantly and positively affect the Value Perception, Green Marketing Mix significantly and positively affect the Intention To Buy, Value Perception significantly and positively affect the Intention To Buy. Green Marketing Mix significantly and positively affect the Intention To Buy throught Value Perception. The Body Shop needs to make the subject of promotion more supportive of environmental exceptions in real terms, for example the program for saving rare animals, holding river cleaning activities or tree planting programs that involve customers directly.Keywords: Green Marketing Mix, Value Perception, Intention To Buy, Cosmetic Product, The Body Shop.